2012
DOI: 10.1371/journal.pone.0044915
|View full text |Cite
|
Sign up to set email alerts
|

Type III Interferons, IL-28 and IL-29, Are Increased in Chronic HCV Infection and Induce Myeloid Dendritic Cell-Mediated FoxP3+ Regulatory T Cells

Abstract: Background & AimsHepatitis C virus (HCV) is difficult to eradicate and type III interferons (IFN-λ, composed of IL-28A, IL-28B and IL-29) are novel therapeutic candidates. We hypothesized that IFN-λ have immunomodulatory effects in HCV- infected individuals.Materials and MethodsWe analyzed the expression of IFN-λ and its receptor (composed of IL-10R2 and IFN-λR subunits) in the blood and livers of patients with chronic (c)HCV infection compared to controls (those who cleared HCV by sustained virological respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 25 publications
3
59
0
2
Order By: Relevance
“…2) IFN-λ may affect T-reg activity. IFN-λ are increased during the chronic stage of HCV and act on DC to stimulate CD4+FoxP3+ T-reg cells (55, 97), perhaps suppressing immune responses to HCV. A novel population of CD4 + FoxP3 + CD25 − T cells make IFN-λ and induce tolerance in a mouse EAE model (98), so potentially these tolerance-inducing populations of cells are induced in the infected WT mice but are diminished in the λR-deficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…2) IFN-λ may affect T-reg activity. IFN-λ are increased during the chronic stage of HCV and act on DC to stimulate CD4+FoxP3+ T-reg cells (55, 97), perhaps suppressing immune responses to HCV. A novel population of CD4 + FoxP3 + CD25 − T cells make IFN-λ and induce tolerance in a mouse EAE model (98), so potentially these tolerance-inducing populations of cells are induced in the infected WT mice but are diminished in the λR-deficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, its expression on hematopoietic cells remains controversial. This issue is discussed in more detail below, but it is generally believed that the main immune cells expressing IFN-λR1 are dendritic cells (DCs) (4, 7, 8). Most studies assessed the expression of IFN-λR1 by polymerase chain reaction (PCR), evaluating the mRNA level, which might not accurately reflect expression of the protein on cell surface.…”
Section: Tissue Tropism Of Type I Versus Type Iii Ifnsmentioning
confidence: 99%
“…Data from the chimp model of HCV infection demonstrated that type III IFNs were strongly induced upon HCV infection at the gene and protein level and correlated with ISG expression and viral load (28). In humans, while some studies associated the favorable IFN-λ3 CC allele with higher serum levels of IFN-λ (29), others demonstrated the reverse correlation (7). One report also found no difference in serum levels of IFN-λ between HCV treatment responders and non-responders (30).…”
Section: Mechanisms Underlying the Role Of Ifn-λ Polymorphisms In Hcvmentioning
confidence: 99%
“…Recent in vitro studies in mice [21] and humans [22], have suggested that IFN-λ promotes the generation of immature dendritic cells (DCs) with tolerogenic activity. IFN-λ-treated DCs specifically induced proliferation and expansion of regulatory T (T reg ) cells which play, a fundamental role in maintaining immune homeostasis.…”
Section: Introductionmentioning
confidence: 99%